f(t) = (1+tan t)^(1/3) differentiate using chain rule.(adsbygoogle = window.adsbygoogle || []).push({});

u = 1 + tan t

y = u^(1/3)

dy/dt = dy/du x du/dt

u=1+tan t

1/3 u^(-2/3) when u = 1 + tan t x sec^(2)t =

= sec^(2)t/3(1+tan t)^(2/3)

Did I do this correct??

**Physics Forums - The Fusion of Science and Community**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Chain Rule

Loading...

Similar Threads for Chain Rule | Date |
---|---|

Demystifying the Chain Rule in Calculus - Comments | Jan 2, 2018 |

I Rigorously understanding chain rule for sum of functions | Aug 6, 2017 |

I Heavyside step function chain rule | Mar 21, 2017 |

B Chain rule problem | Feb 26, 2017 |

B Chain rule for variable exponents | Jan 30, 2017 |

**Physics Forums - The Fusion of Science and Community**